Relationship of parental feeding practices and diet with children's diet among South Asians in Canada - Slapnicar, Calum; Lear, Scott A.; Dehghan, Mahshid; Gupta, Milan; Rangarajan, Sumathy; Punthakee, Zubin (Appetite, 2022)
South Asian children's diets are considered unhealthy, yet the relationship with food parenting among South Asians is understudied. In a cross-sectional study, questionnaires were administered to dyads of Canadian South Asian elementary and high school children and a parent. Relationships between parental factors (perceived responsibility, restriction, pressure to eat, monitoring, home food environment, nutrition knowledge and intake of fruits and vegetables (FV), sugary beverages (SB) and sweets and fast foods (SWFF) and children's intake of FV, SB and SWFF were assessed by linear regression adjusted for sociodemographics. Subgroup differences by children's age and acculturation were explored by interaction analysis. 291 children (age 9.8 ± 3.2 years) had mean daily intake frequencies of 3.1 ± 2.0 FV, 1.0 ± 0.9 SB and 2.1 ± 1.5 SWFF. Positive associations were found between parent and child intake of FV (standardized beta (ß) = 0.230, [95%CI 0.115, 0.345], p < 0.001), SB (β = 0.136 [0.019, 0.252], p = 0.02), and SWFF (β = 0.167 [0.052, 0.282], p = 0.005). Parental monitoring was associated with lower children's SWFF intake (ß = −0.131 [-0.248, −0.015], p = 0.03). Among those expressing less Western culture, parental SWFF intake was associated with child's SB intake (β = 0.255 [0.085, 0.425], p = 0.004). Among those expressing less traditional culture, positive home food environment was associated with lower child SWFF intake (β = −0.208 [-0.374, −0.042], p = 0.015). South Asian children's diets have stronger relationships with their parents' diets than with food parenting practices or nutrition knowledge, though parental monitoring was associated with lower unhealthy food intake. However, with greater acculturation, the home food environment was more important for unhealthy food intake.